Progress Report to The IMFC On the Activities Of The Independent Evaluation Office Of The IMF. (Policy Papers; Policy Paper ;, 2020)
Like everyone else, the IEO is now adapting to new realities in the wake of the coronavirus pandemic. During the five months after the 2019 Annual Meetings, the IEO completed two reports, continued work on two ongoing evaluations, and launched one new evaluation. The IMF also made good progress in following up on past IEO evaluations, including completion of a triage exercise aimed at dealing with the backlog of off-track actions. Unfortunately, IEO work plans are now being affected by the current crisis, as the Fund's work is necessarily dominated by the challenge of meeting members' urgent needs. Planned IEO engagement with the Board has been delayed and the schedule for ongoing and new evaluations has to be extended. Nevertheless, the IEO will continue to advance its work program as best it can within the new constraints.